Fifteen-year Follow-up of a Conservatively Managed, Root-fractured Permanent Incisor - Borges, Alvaro Henrique; Sakai, Vivien Thiemy; Salgueiro, Carla Eremita; Barbosa e Silva, Nathalia; Bueno, Mike dos Reis; Bandeca, Matheus Coelho (Amer Acad Pediatric Dentistry, 2012)
The purpose of this case report was to describe the successful long-term conservative management of a root-fractured permanent maxillary right central incisor in an 8-year-old patient. After the initial approach of splinting the traumatized tooth, the patient was followed on a regular basis for 15 years. Clinically, the crown of the root-fractured incisor showed no displacement or discoloration, and thermal tests suggested pulp vitality over the follow-up period. Radiographically, an increase in the diastasis was observed between the apical and coronal fragments due to both the growth of the alveolar process and the healing with interposition of hard and soft tissue between the fragments and confirmed with computed tomography scan in the 15-year follow-up appointment. (Pediatr Dent 2012;34:156-8) Received June 21, 2010 vertical bar Lost Revision August 18, 2010 vertical bar Accepted August 27, 2010
Keywords: DENTAL TRAUMA; PERMANENT TOOTH; TOOTH INJURY